Strategi Komunikasi Pemasaran dalam Menjaga Hubungan Baik dengan Pemangku Kepentingan Eksternal: Studi Kasus Swiss-Belhotel Bandara Jakarta Soekarno Hatta - Eka Putra, Ahmad Septian; Rini Hardiyanti; Luna Safitri Salsabil (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research is about the strategy of Marketing Communication at Swissbel-Hotel Jakarta Soekarno Hatta Airport in maintaining good relations with external stakeholders. The purpose of this study is to find out the strategy of Marketing Communication at Swissbel-Hotel Jakarta Soekarno Hatta Airport in maintaining good relations with external stakeholders. The problem of this research is how to implement the Marketing Communication strategy strategy at Swissbel-Hotel Jakarta Soekarno Hatta Airport in maintaining good relations with external stakeholders. The method used in this study to analyze the problems in this study is a qualitative research method of case studies. The theory used in this study is Public Relations Theory by Cutlip & Center (2003) with four stages of fact finding, planning and programming, communication, and evaluation strategies. The subject of this research is Marketing Communication at Swissbel-Hotel Jakarta Soekarno Hatta Airport and the object of this research is focused on the application of Marketing Communication strategies in maintaining good relations with external stakeholders. The researcher presents data information collected from both the internal and external sides of the company, observation of non-participant analysis, as well as semi-structured interviews with several sources related to this research problem. The conclusion of this study is that in carrying out a public relations strategy to maintain good relations with partners, Swissbel-Hotel Marketing Communication emphasizes on fact finding, planning and programming, communication, and evaluation.